The Effect of Current Density on Mechanical Properties of Electroplated Thin Copper Foil - Luthfi Luthfi; Yuniati Yuniati; Darmein Darmein; Sumardi Sumardi (Politeknik Negeri Lhokseumawe, 2023)
Thin copper foils are commonly used in arts, crafts, and manufacturing industries. Although copper electroplating processes have been widely studied, most focused on either copper in bulk material form factor or copper in extremely thin film shape. Thin copper foils are considered neither bulk material nor thin film; thus, it is estimated that they will have unique properties. This study aims to investigate the mechanical properties of thin copper foils coated by electroplating processes. The investigations were conducted experimentally by performing electroplating at current densities of 2, 3, and 4 A/dm2. The copper foil specimen having a dimension of 10 mm wide, 0.2 mm thick, and 125 mm long were electroplated in a bath of copper sulfate, sulfate acid, chloride acid, and copper brightener mixtures for 60 minutes powered by a 30 A DC power supply. The hardness and tensile test diagrams were studied. The strain, yield stress, and ultimate tensile stress data extracted from the tensile test diagram were compared with other previous studies found in the literature and fitted with linear regression lines. The relationship of those parameters with current density has been successfully obtained. The hardness, strain, and yield stress of the electroplated copper foil increased with larger current densities used in the electroplating process except for the ultimate tensile stress, which was found to be slightly decreased with current densities. The optimum operating condition for obtaining the best results was found at a current density of 3 A/dm2.